Perancangan dan Pemodelan Basis Data Terintegrasi untuk Sistem Informasi Kursus Bahasa Jepang Online - Muhammad Mulia Wahiddin Harahap; Bekti Nur Wicaksono; Rassya Mahesar Arroviq; Zatin Niqotaini (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2026)
Digital transformation in the education sector has accelerated the growth of internet-based learning platforms that offer learners greater flexibility in accessing educational content. Among the various foreign language programs available online, Japanese language courses have gained considerable popularity due to their ability to provide unrestricted learning access regardless of location or time. However, course providers frequently encounter significant data governance challenges, including inconsistent record-keeping, data duplication, and the fragmentation of learner information, class schedules, payment transactions, attendance records, assessment results, and certificate issuance across disconnected systems. These issues impede efficient data retrieval and reporting, while reliance on manual recording processes raises the risk of errors and delays. This study focuses on constructing a database architecture for an online Japanese language course information system, with the primary objective of achieving data consolidation and enhancing the quality of operational information management. The modeling approach encompasses three stages: entity mapping through an Entity Relationship Diagram (ERD), conceptual structuring via a Conceptual Data Model (CDM), and physical implementation using a Physical Data Model (PDM), complemented by a visual monitoring dashboard design for administrators. The findings demonstrate that a well-structured and integrated database design successfully consolidates all operational course data into a single centralized repository, substantially reduces data duplication, and streamlines the processes of management, visual monitoring, and information reporting within the online Japanese language course platform.